2023
DOI: 10.3390/app13148485
|View full text |Cite
|
Sign up to set email alerts
|

Use of Logarithmic Rates in Multi-Armed Bandit-Based Transmission Rate Control Embracing Frame Aggregations in Wireless Networks

Abstract: Herein, we propose the use of the logarithmic values of data transmission rates for multi-armed bandit (MAB) algorithms that adjust the modulation and coding scheme (MCS) levels of data packets in carrier-sensing multiple access/collision avoidance (CSMA/CA) wireless networks. We argue that the utilities of the data transmission rates of the MCS levels may not be proportional to their nominal values and suggest using their logarithmic values instead of directly using their data transmission rates when MAB algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The proposed method determines the most suitable modulation and coding scheme (MCS) for future transmission based on the shifts in received signal-to-noise ratio (SNR) with time. In [8], the authors aimed to more precisely manage the transmission rates in CSMA/CA wireless networks by employing MAB algorithms. The authors suggested using the logarithmic values of the transmission rates of MCS levels rather than their nominal values in the computation of their anticipated throughput measures.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method determines the most suitable modulation and coding scheme (MCS) for future transmission based on the shifts in received signal-to-noise ratio (SNR) with time. In [8], the authors aimed to more precisely manage the transmission rates in CSMA/CA wireless networks by employing MAB algorithms. The authors suggested using the logarithmic values of the transmission rates of MCS levels rather than their nominal values in the computation of their anticipated throughput measures.…”
Section: Introductionmentioning
confidence: 99%